Undular Hydraulic Jump - Oscar Castro-Orgaz; José Roldán; José Dolz (Ingeniería del Agua)
The transition from subcritical to supercritical flow when the inflow Froude number Fo is close to unity appears in the form of steady state waves called undular hydraulic jump. The characterization of the undular hydraulic jump is complex due to the existence of a non-hydrostatic pressure distribution that invalidates the gradually-varied flow theory, and supercritical shock waves. The objective of this work is to present a mathematical model for the undular hydraulic jump obtained from an approximate integration of the Reynolds equations for turbulent flow assuming that the Reynolds number R is high. Simple analytical solutions are presented to reveal the physics of the theory, and a numerical model is used to integrate the complete equations. The limit of application of the theory is discussed using a wave breaking condition for the inception of a surface roller. The validity of the mathematical predictions is critically assessed using physical data, thereby revealing aspects on which more research is needed